Memorandum on the Programme of Research for the Development of National Resources - Planning Commission (Planning Commission, 1956)
The Panel of Scientists was constituted in April, 1956, to advise and assist the Planning Commission in linking up programmes of scientific study and investigations in the national laboratories, in universities and in many institutions which are maintained and supported by Government, as closely as possible, with the requirements of national planning. The setting up of the Panel was itself an occasion of some significance, because with the Second Five-Year Plan, the country has entered a crucial phase in its industrial and technological progress, and in every field of social and economic development, there are problems pressing for solution and for new knowledge.
Planning Commission Panel of Scientists
Planning Commission Panel of Scientists